Cisplatin activates volume sensitive LRRC8 channel mediated currents in Xenopus oocytes. Issue 3 (4th May 2017) - Gradogna, Antonella; Gaitán-Peñas, Héctor; Boccaccio, Anna; Estévez, Raúl; Pusch, Michael
ABSTRACT: LRRC8 proteins have been shown to underlie the ubiquitous volume regulated anion channel (VRAC). VRAC channels are composed of the LRRC8A subunit and at least one among the LRRC8B-E subunits. In addition to their role in volume regulation, LRRC8 proteins have been implicated in the uptake of chemotherapeutic agents. We had found that LRRC8 channels can be conveniently expressed in Xenopus oocytes, a system without endogenous VRAC activity. The fusion with fluorescent proteins yielded constitutive activity for A/C, A/D and A/E heteromers. Here we tested the effect of the anticancer drug cisplatin on LRRC8A-VFP/8E-mCherry and LRRC8A-VFP/8D-mCherry co-expressing oocytes. Incubation with cisplatin dramatically activated currents for both subunit combinations, confirming that VRAC channels provide an uptake pathway for cisplatin and that intracellular cisplatin accumulation strongly activates the channels. Thus, specific activators of LRRC8 proteins might be useful tools to counteract chemotherapeutic drug resistance.